1997
DOI: 10.1128/cmr.10.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial persistence and expression of disease

Abstract: A considerable body of experimental and clinical evidence supports the concept that difficult-to-culture and dormant bacteria are involved in latency of infection and that these persistent bacteria may be pathogenic. This review includes details on the diverse forms and functions of individual bacteria and attempts to make this information relevant to the care of patients. A series of experimental studies involving host-bacterium interactions illustrates the probability that most bacteria exposed to a deleteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 123 publications
6
129
0
Order By: Relevance
“…Interestingly, persistence in macrophages has also been reported for S. aureus L-forms. After intra-phagosomal formation of S. aureus L-forms in alveolar macrophages of rats, the phagocytes were incapable of lysosomal acid-phosphatase activation and phagosome-lysosome fusion (Michailova et al, 2007), which could suggest that these L-forms may represent persisters (Beaman and Scates, 1981; Domingue and Woody, 1997). Consequently, the wall-less state of bacteria had been speculated to possibly assume roles in chronic disease, based on the lack of immune recognition (Domingue and Woody, 1997; Domingue, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, persistence in macrophages has also been reported for S. aureus L-forms. After intra-phagosomal formation of S. aureus L-forms in alveolar macrophages of rats, the phagocytes were incapable of lysosomal acid-phosphatase activation and phagosome-lysosome fusion (Michailova et al, 2007), which could suggest that these L-forms may represent persisters (Beaman and Scates, 1981; Domingue and Woody, 1997). Consequently, the wall-less state of bacteria had been speculated to possibly assume roles in chronic disease, based on the lack of immune recognition (Domingue and Woody, 1997; Domingue, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The inability of most research labs to culture cell wall deficient (CWD) bacteria has been an obstacle to their acceptance, and reliance on Koch’s postulates has made it difficult to correlate CWD bacteria to specific diseases [72]. But some researchers believe Koch’s postulates may have to be redefined in terms of molecular data when dormant and non-culturable bacteria are implicated as causative agents of mysterious diseases [73]. O´Connor et al [74] (in their article entitled Emerging Infectious Determinants of Chronic Diseases) report, “microbes can now be irrefutably linked to pathology without meeting Koch’s postulates” and “…powerful tools of molecular biology have exposed new causal links by detecting difficult-to-culture and novel agents in chronic illness settings.”…”
Section: Low Vitamin D Is Found In Healthy Subjectsmentioning
confidence: 99%
“…Many microbiologists now believe at least some, if not all, of the inflammation which drives the chronic disease process is caused by the presence of these stealthy intracellular pathogens [86]. A considerable body of experimental and clinical evidence supports the concept that difficult-to-culture and dormant bacteria are involved in latency of infection and that these persistent bacteria may be pathogenic [73, 87, 88]. McDougal [89] states, “Evidence now confirms that non-communicable chronic diseases can stem from infectious agents.”…”
Section: Low Vitamin D Is Found In Healthy Subjectsmentioning
confidence: 99%
“…The mechanisms of Nocardia pathogenesis are complex and not fully understood (Domingue and Woody 1997). In N. asteroides, the studies showed relative virulence correlated with many factors, such as the abilities to inhibit phagosome-lysosome fusion in phagocytes; to neutralize phagosomal acidification; to detoxify the microbicidal products of oxidative metabolism; to modify phagocyte function; to grow within phagocytic cells; and to attach to, penetrate, and grow within host cells (Beaman and Beaman 1994).…”
Section: Introductionmentioning
confidence: 99%